Outcomes of pregnancy in women with hypertrophic cardiomyopathy: A systematic review. (15th July 2022) - Moolla, Muhammad; Mathew, Anoop; John, Kevin; Yogasundaram, Haran; Alhumaid, Waleed; Campbell, Sandra; Windram, Jonathan
Abstract: Introduction: Hypertrophic cardiomyopathy (HCM) is a genetic disorder that can be complicated by heart failure and sudden cardiac death. Pregnancy causes hemodynamic changes, which may be deleterious in patients with HCM. Existing cohort studies, analyzing maternal and fetal outcomes of pregnant HCM patients, are limited by small sample sizes. We performed a systematic review of maternal and fetal outcomes of pregnancy in patients with HCM. Methods: We performed a literature search for studies reporting maternal or fetal outcomes in pregnant women with HCM. Primary outcomes included maternal death, stillbirth, and fetal death. Secondary maternal outcomes included both sustained and non-sustained ventricular tachycardia (VT), atrial fibrillation, heart failure (HF), syncope, cesarean delivery, and preeclampsia/eclampsia. The secondary fetal outcome was preterm birth. We used a random-effects model to determine pooled incidences of outcomes. Results: We identified a total of 18 studies with 1624 pregnancies. The incidence of maternal death was 0.2%. The rates of sustained VT, any VT (including non-sustained), AF, HF, and syncope were 1% (0–1%), 6% (4–8%), 4% (2–6%), 5% (3–8%), and 9% (3–14%), respectively. Postpartum hemorrhage, preeclampsia/eclampsia, and cesarean section complicated 2% (1–4%), 4% (2–6%), and 43% (32–54%) of pregnancies, respectively. Neonatal death occurred in 0.2% of pregnancies. Stillbirth complicated 1% (95% CI, 0–3%) of pregnancies, whereas the incidence of preterm birth was 22% (95% CI, 18–25%). Conclusions: Women with HCM considering pregnancy can be reassured that the risk of maternal, fetal, or neonatal death is low. However, they are at risk of several non-fatal cardiac and pregnancy-related complications. Highlights: This is the first comprehensive review of pregnancy and hypertrophic cardiomyopathy Pregnant women with hypertrophic cardiomyopathy have an overall low risk of death They are at risk for several cardiac and pregnancy related complications They may benefit from individualized care within a cardiac obstetric program